Implementation research to support Bangladesh Ministry of Health and Family Welfare to implement its national guidelines for management of infections in young infants in two rural districts - Salahuddin Ahmed; Jennifer A. Applegate; Dipak K. Mitra; Jennifer A. Callaghan-Koru; Mahfuza Mousumi; Ahad Mahmud Khan; Taufique Joarder; Meagan Harrison; Sabbir Ahmed; Nazma Begum; Abdul Quaiyum; Joby George; et al. (BMC, 2019)
Abstract Background World Health Organization revised the global guidelines for management of possible serious bacterial infection (PSBI) in young infants to recommend the use of simplified antibiotic therapy in settings where access to hospital care is not possible. The Bangladesh Ministry of Health and Family Welfare (MoHFW), Government of Bangladesh (GOB) adopted these guidelines, allowing treatment at first-level facilities. During the first year of implementation, the Projahnmo Study Group and USAID/MaMoni Health Systems Strengthening (HSS) Project supported the MoHFW to operationalize the new guidelines and conducted an implementation research study in selected districts to assess challenges and identify solutions to facilitate scale-up across the country. Implementation support Projahnmo and MaMoni HSS teams supported implementation in three areas: building capacity, strengthening service delivery, and mobilizing communities. Capacity building focused on training paramedics to conduct outpatient management of PSBI cases and developing monitoring and supervision systems. The teams also filled gaps in government supply of essential drugs, equipment, and logistics. Community mobilization strategies to promote care-seeking and referrals to facilities varied across districts; in one district community, health workers made home visits while in another district, the promotion was carried out through community volunteers, village doctors, and through existing community structures. Methods We followed a plan-do-study-act (PDSA) cycle to identify and address implementation challenges. Three cycles-1 every 4 months-were conducted. We collected data utilizing quantitative and qualitative methods in both the community and facilities. The total sample size for this study was 13,590. Discussion This article provides implementation research design details for program managers intending to implement new guidelines on management of young infant infections. Results of this research will be reported in the forthcoming papers. Preliminary findings indicate that the management of PSBI cases at the UH&FWCs is feasible. However, MoHFW, GOB needs to address the implementation challenges before scale-up of this policy to the national level.